Incomplete penetrance and variable phenotypes of a novel NPRL2 frameshift variant: from familial focal epilepsy with variable foci 2 to neurodevelopmental disorders - Hui Zhu; Qiyan Wang; Wenxin Deng; Shuyao Zhu; Lan Zeng; Ai Chen; Ying Pang; Fu Xiong (BMC Neurology)
Abstract Background Familial focal epilepsy with variable foci 2 (FFEVF2), an autosomal dominant disorder caused by pathogenic heterozygous variants in the NPRL2 gene, is characterized by focal epilepsy originating in different cortical regions of the temporal, frontal, parietal, and occipital lobes of the brain. Methods The study included a Chinese family in which proband had epilepsy, and her brother had autism, attention deficit hyperactivity disorder (ADHD), and mild intellectual disability (ID). Blood samples of the two children and their parents were collected for whole exome sequencing (WES). Results Proband was a 1-month-and-7-day-old baby girl with epilepsy manifesting as focal to bilateral tonic-clonic seizures and cranial magnetic resonance imaging showing focal cortical dysplasia or subcortical grey matter ectopia in the left anterior and posterior central gyrus. WES revealed a heterozygous variant of the NPRL2 gene [c.907delC (p. Gln303Serfs*11)]. Sanger sequencing confirmed that the variant was inherited from her unaffected mother. According to the ACMG, the variant was classified as likely pathogenic. Finally, she was diagnosed with FFEVF2. Her epilepsy type was only reported in one patient with FFEVF2 with multiple seizure types. Follow-up revealed that she had a global developmental delay and absent language, and despite numerous antiseizure medications, her seizures were uncontrolled. Her brother carried the same mutated gene, which manifested primarily as autism, ADHD, speech deficit, and mild ID. So far, he has had no seizures and a negative electroencephalogram. But he could have seizures in the future, and it’s worth following up. Conclusion This study describes a family with a new NPRL2 variant, where affected members exhibited various neurological disorders including FFEVF2, autism, and ADHD, demonstrating incomplete penetrance.